The Role of Experiential Learning on Students’ Motivation and Classroom Engagement - Kong, Yangtao (Frontiers in Psychology, 2021)
Due to the birth of positive psychology in the process of education, classroom engagement has been flourished and got a remarkable role in the academic field. The other significant determining factor of success in education is motivation which is in line with classroom engagement. Moreover, based on the constructivist approach, experiential learning (EL) as a new method in education and a learner-centric pedagogy, is at the center of attention, as a result of its contributions to improving the value of education which centers on developing abilities, and experiences. The current review makes an effort to consider the role of EL on students’ classroom engagement and motivation by inspecting its backgrounds and values. Subsequently, the efficacy of findings for academic experts in educational contexts is discussed.